2022
DOI: 10.1136/bmjmilitary-2022-002128
|View full text |Cite
|
Sign up to set email alerts
|

Addressing moral injury in the military

Abstract: Moral injury is a relatively new, but increasingly studied, construct in the field of mental health, particularly in relation to current and ex-serving military personnel. Moral injury refers to the enduring psychosocial, spiritual or ethical harms that can result from exposure to high-stakes events that strongly clash with one’s moral beliefs. There is a pressing need for further research to advance understanding of the nature of moral injury; its relationship to mental disorders such as posttraumatic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Despite the increasing consensus that MI is a unique type of psychological stressor, there is an ongoing debate about best practices for treatment (Griffin et al, 2019). Although, it is argued that evidence‐based PTSD treatments could be sufficient (Held et al, 2018), some disagree (Litz et al, 2016; Phelps et al, 2022). For example, previous research suggested that prolonged exposure (PE) could potentially be harmful in cases of MI and exacerbate patient reactions of shame, disgust and guilt (Maguen & Burkman, 2013), however, in a recent systematic review cognitive‐based treatments were found to effectively reduce symptoms of guilt and anger, while exposure‐based treatments appeared effective for symptoms of guilt, shame and anger (Serfioti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing consensus that MI is a unique type of psychological stressor, there is an ongoing debate about best practices for treatment (Griffin et al, 2019). Although, it is argued that evidence‐based PTSD treatments could be sufficient (Held et al, 2018), some disagree (Litz et al, 2016; Phelps et al, 2022). For example, previous research suggested that prolonged exposure (PE) could potentially be harmful in cases of MI and exacerbate patient reactions of shame, disgust and guilt (Maguen & Burkman, 2013), however, in a recent systematic review cognitive‐based treatments were found to effectively reduce symptoms of guilt and anger, while exposure‐based treatments appeared effective for symptoms of guilt, shame and anger (Serfioti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One such significant cognitive state is moral injury (MI), which has not gained much attention in the literature of bullying nor been proposed as one of the consequences of bullying in a general sense. It has been studied so far by law scholars and psychologists in the military context (Phelps et al ., 2022). MI is defined as the profound distress that follows an occurrence in which one's core moral beliefs have been violated by a person in a superior role—or by oneself—in a situation where the stakes are high (Anderson and MFTC, 2021; Shay, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a manualised treatment, lower clinician confidence in treating cases of moral injury (Phelps et al, 2022 ; Williamson et al, 2019 ; Williamson et al, 2021b ) and the significant associations found between PMIE exposure and suicidality suggests that moral injury may represent an important public health concern. Whilst there is some early evidence of potential treatments for moral injury related mental health difficulties in the USA, such as ‘The Impact of Killing’ treatment (Maguen et al, 2017 ; Purcell et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%